DESIGNING MULTIMEDIA FOR LECTURERS NEED IN TEACHING ENGLISH PRONUNCIATION - Damayanti Sri (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2014)
The objectives of this research are to find out the students error in pronunciang some selected English words and to design multimedia based on the students need in teaching pronunciation. The researcher took 8 students as sample randomly of 300 students at English Education Study program of Cokroaminoto Palopo University. This research tries to develop of some theories in Phonology and create or design the media (multimedia) in teaching pronunciation. The result of this research shows the students error in pronouncing vowel, diphthong, and Consonant when they find the word which is not familiar with them and when they find the word which consists of sound that is not exist in Indonesian sound. So, the design of media in teaching English Pronunciation is multimedia which consists of some materials in vowel, consonant, and diphthong. This media also provides sounds in pronouncing some English words.